Experimental Study of Permeability Characteristics of Bamboo Betung Activated Carbon as Alternative Pad Material for Direct Evaporative Cooling System - I Made Feby Arya Putra; Hendra Wijaksana; I Gede Teddy Prananda Surya (HM Publisher, 2023)
The increased growth in the building sector, especially in big cities, has triggered an increase in the need for electrical energy for cooling systems, most of which use compressor-based cooling systems. Direct Evaporative Cooling (DEC) is evaporative that produces cooling by utilizing the latent heat of evaporation of water on the wet surface of the pad material. The pad material must be sufficiently porous to allow the free flow of air through it and must have a large enough wet surface area. This study used carbonized and activated bamboo Betung as a material for the DEC system. The research was conducted to obtain the permeability characteristics of the carbonized bamboo pad material at various temperatures of 400oC, 500oC 600oC, 700oC, and 800oC and then activated at a temperature of 600oC with a holding time of 60 minutes. Based on the results of the research on the permeability characteristics of bamboo Betung activated carbon material, which was carbonized at a temperature of 400oC and activated at a temperature of 600oC with a holding time of 60 minutes (ABR 400) had the highest permeability of 13.6 x 10-15 m2. Meanwhile, the lowest permeability was produced by bamboo Betung material which was carbonized at a temperature of 800oC and activated at an activation temperature of 600oC with a holding time of 60 minutes (ABR 800) which is only 0.56x10-15 m2.